”Nån slags soffliggande nomad i musikbranschen”: Ett samtal med Max Mackhé om musik, identitet och politisk aktivism - Nordström, Marika (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2014)
This article presents Max Mackhé, a pop musician and political activist. He comes from Sweden, lives in Norway and feels like part of the Sámi community. The article discusses Max’s own experiences concerning identity and shows how an ethnic identity can be culturally constructed and that this can be a complex issue that relates to civil rights, among other things. Early in his life he felt affinity towards the Sámi culture and has witnessed racism toward Sámi people. His music nowadays bears witness of his strong political engagement in environmental issues and the rights of indigenous peoples, for instance regarding the current mining exploitations in the north of Sweden. His political activism also takes place in social media, for instance on Twitter.